Is There Enough Redistribution? - Eden, Maya (World Bank, Washington, DC, 2017)
This paper asks whether there are welfare gains from additional redistribution. First, it derives a sufficient condition for the existence of welfare gains from a small increase in lump-sum transfers financed by a uniform increase in labor income taxes. A calibration suggests that, even under very conservative assumptions, most countries would benefit from such a scheme. Second, it asks whether, given existing tax revenues, there are gains from diverting public funds from government investment projects toward redistributive programs. The analysis suggests that the answer is highly sensitive to parameter values and the rate of return on government investment.